Problematika Dakwah Humor: Antara Daya Tarik Dan Dangkalnya Substansi (Tinjauan Epistimologis Terhadap Teologi Transformatif Dan Retorika Populer) - Ayu Trysnawati; Suf Kasman; Ramsiah Tasruddin (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
This The phenomenon of humorous da’wah (religious outreach) in a contemporary context reveals a significant shift in religious communication practices, particularly amidst the dominance of popular culture and digital media. This article aims to analyze the issues surrounding humorous da’wah from an epistemological perspective, highlighting the tension between popular rhetorical appeal and the depth of theological substance within the framework of transformative theology. Employing a qualitative approach and descriptive-analytical library research, the study examines scholarly literature on contemporary da’wah, humor, and religious communication published over the last five years. The finding indicate that humor in da’wah has transformed from a mere rhetorical technique into a communication paradigm that shapes the construction of religious knowledge. Humor serves as an effective mechanism for cognitive and affective simplification, bridging the gap between complex theological teachings and the audience's reality. However, the dominance of humor also triggers an epistemological shift, wherein the validity of the message is determined more by audience response than by substantive depth. Furthermore, humorous da’wah has become integrated into the logic of the digital cultural industry, leading to commodification that threatens to shift the orientation of da’wah from education to entertainment. This phenomenon implies a trend of theological de-substantiation, where religious messages become superficial due to the dominance of popular rhetoric. Consequently, this study emphasizes the importance of formulating ethical communication guidelines for the use of humor in da’wah. Humor must be positioned as an instrument rather than a primary goal, while remaining grounded in prophetic values ​​that foster liberation and critical awareness. Thus, a synthesis between transformative theology and popular rhetoric can be achieved by balancing communicative appeal with theological depth.